1998
DOI: 10.1016/s0014-5793(98)00406-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological dynamics and distribution of 3‐hydroxy fatty acids in the yeast Dipodascopsis uninucleata as investigated by immunofluorescence microscopy. Evidence for a putative regulatory role in the sexual reproductive cycle1

Abstract: Dipodascopsis uninucleata has been recently shown to produce 3-hydroxy polyenoic fatty acids from several exogenous polyenoic fatty acids. In order to examine whether endogenous 3-hydroxy fatty acids (3-OH-FA) may be implicated in the developmental biology of this yeast, we mapped by immunofluorescence microscopy their occurrence in fixed cells with or without cell walls using an antibody raised against 3R-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (3R-HETE), the biotransformation product from arachidonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 16 publications
4
55
0
Order By: Relevance
“…Although many studies have focused on C 18 oxylipins, several experiments have revealed that both pathogenic and nonpathogenic fungal species produce detectable amounts of both C 20 cyclooxygenase and lipoxygenase products (36,44,45). The arachidonic acid metabolites PGF 2 and PGF 2 -lactone have been detected in a number of environmental yeasts of the family Lipomycetaceae (Dipodascopsis, Lipomyces, Myxozyma, and Zygozyma) (22,33,34,55) as well as in Saccharomyces cerevisiae (33). The pathogenic yeasts Cryptococcus neoformans and Candida albicans and the filamentous fungus A. fumigatus produce both PGs and leukotrienes, and their amounts are significantly increased after exogenous application of arachidonic acid (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on C 18 oxylipins, several experiments have revealed that both pathogenic and nonpathogenic fungal species produce detectable amounts of both C 20 cyclooxygenase and lipoxygenase products (36,44,45). The arachidonic acid metabolites PGF 2 and PGF 2 -lactone have been detected in a number of environmental yeasts of the family Lipomycetaceae (Dipodascopsis, Lipomyces, Myxozyma, and Zygozyma) (22,33,34,55) as well as in Saccharomyces cerevisiae (33). The pathogenic yeasts Cryptococcus neoformans and Candida albicans and the filamentous fungus A. fumigatus produce both PGs and leukotrienes, and their amounts are significantly increased after exogenous application of arachidonic acid (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…With the characterization of ppoA and ppoC, we provide evidence of an endogenous system balancing meiospore and mitospore production in A. nidulans. Orthologs of both of these genes are found in filamentous fungi and, coupled with the numerous studies linking oxylipin production with fungal sporulation (27,31,33,42,51), support a case for conservation of an oxylipin-driven mechanism controlling, among other cellular processes, sexual and asexual differentiation. We propose that fungal oxylipins serve as autocrine or paracrine signals generated in response to-and enabling the fungus to respond appropriately to-specific environmental parameters.…”
mentioning
confidence: 88%
“…It is interesting to note that the specific 3-OH oxylipin species present are different depending on the strains and the growth conditions (Table II) It is now necessary to produce significant amounts of pure 3-OH 8:0, either through biotechnological processes using the appropriate yeast strain, or through chemical procedures 5,8 , and determine whether the addition of this oxylipin will uplift the inhibitory effect of aspirin, or perhaps enhance co-flocculation. This would be of importance to the fermentation industry where control of flocculation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence of co-flocculating cells (Table I: G-J) were performed as described 8 . This included treatment with the primary antibody against 3-OH oxylipins as well as FITC conjugated secondary antibody.…”
Section: Immunofluorescence Studiesmentioning
confidence: 99%